Clínica como Comunidade de Destino numa perspectiva ética, estética e política. - Fonsêca, Cícero José Barbosa da (2018)
This dissertation aimed to reflect, from theoretical, the possibility of a clinic as a community of destiny. To do so, we are dealing with issues relating to transformations that we experience in modernity, in the face of which are necessary inovadas ways of understanding of human existence that can give support to the sufferings of man in the days of today. In this respect, it was observed, generating experiences a deep malaise configurator, a subject marked by threefold tyranny of technology, consumption and information, crossed by a logic of utility- Discardability-speed generators, feelings of helplessness and existential dyspepsia, a condition of deep uprooting shaft of ethical fractures by plunging the human in situations in which the other lack frighteningly and exacerbates the experience of being at the mercy. Forward to this context, there is, in actuality, a movement of conceiving and exercising the clinic as a community of destiny, characterized by an attitude that both welcomes the appearance of the person as he transmits the elements available and required for this access a meaning to their existence - a clinic in which human issues and existential permeate the whole course of treatment. Perspective that requires an integral approach of the human and a knowledge embedded in which life is not divided, demanding the clinician that he show his humanity, with provision to inhabit the paradox, at a time conducive to your disposal. Condition that plunges our time on devices intended to administer the life through strategies of government of life, such as the militarisation, medicalization and judicialization that subtract from the unutterable and the mysteries of his being. In this context, we realize it is essential that the clinician to recognize and accept the fundamental elements of the human condition- a clinic as a community of destiny anchored in Great Ethics, in the Great Aesthetics and in major Politics, as proposed in this work. A clinic founded in the state of tension constitutive of human, as a condition that allows the life pulsate and, at the same time and at the same time, who calls us to create and affirm a mode of being as possibility of venturing in bustling procedures of life. Finally, a clinic as a process of redemption of the opening State essential at a time of profound funcionalização of existence that transforms the beautiful in insurance, the dialog in a monologue and the diversity in disorder. A clinic understood, experienced and too committed to the existence, whose primary objective is to create conditions that allow what is prevented from having (the body, the senses and the world) find avenues of expression. There was a need for research that will extend this debate about this possibility to practice medicine, due to the scarcity of bibliographic material in psychology in relation to this issue.